The Effect of Teams Games Tournament (TGT) Cooperative Learning Model Assisted by Educandy Application on Student Learning Outcomes on Ecology Material - Rizschy Nurfauzie Al-Ma'shum; Milla Listiawati; Astri Yuliawati (Jurnal Impresi Indonesia, 2024)
The learning model is one of the causes of the lack of student motivation in learning problems so that it affects student learning outcomes. The use of the right learning model is one of the determinants of success in learning activities carried out by teachers. This study aims to analyze the effect of TGT learning model assisted by educandy on student learning outcomes on ecology material. This research uses a quantitative approach with a quasi-experimental design. The sample amounted to 28 students selected through cluster random sampling technique. Cognitive aspect learning outcomes were obtained through pretest and posttest. Learning ecology material through the TGT model assisted by educandy makes students participate actively so that the learning stages are carried out very well. The cognitive learning outcomes of students using the TGT model assisted by educandy obtained a score of 82 with an n-gain value of 0.62 with moderate criteria. While in the control class, students' cognitive learning outcomes obtained a score of 70 and an n-gain value of 0.45 with a moderate category. The results of the t-test analysis obtained a significant value of 0.000 <0.005 means the hypothesis is accepted. There is an effect of TGT learning model assisted by educandy application on student learning outcomes on ecology material.